Transnational Organized Crime and Future Threats in Bangladesh: Comparative Combating Measures - Jahan, Bushrat (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
Bangladesh is a South Asian country having become independent recently and confronting countless crimes, and transnational coordinated crime is one of them. With the proliferation of criminal associations and the accessibility of present-day digitalization, the level of transnational danger has increased in an alarming way, where just a coordinated and elevated degree of globally approved cooperation can resolve the issue. Transnational organized crime increases border tensions and danger also. In this paper, I will focus on a few explicit transnational crimes occurring in Bangladesh and how those can be a future danger to the existence of this country. Border hostility, arms dealing, drug trafficking, and illegal human exploitation have been persistent security dangers to the country. I will likewise concentrate on some combating measures taken by the EU to control transnational organized crimes and a comparative discussion of how Bangladesh ought to step up measures to control such crimes in the future.